PENCEGAHAN STROKE SEDINI MUNGKIN MELALUI EDUKASI, PENGUKURAN KUALITAS HIDUP DAN PELATIHAN SENAM ANTISTROKE-ANTISTRESS DI PUSKESMAS TLOGOSARI KULON SEMARANG - Muslimah Muslimah; Nina Anggraeni Noviasari; Wijayanti Fuad; Rochman Basuki; Ghina Nur Shafira; Ricco Muhammad Syaifuddin; Zenia Meyra Maharani (Jurnal Pengabdian Sosial, 2023)
ABSTRACT Stroke is the third leading cause of death after coronary heart disease. The prevalence of stroke cases in Central Java is 3.09%. Stroke can affect the patient's life in physical, emotional, psychological, cognitive, and social aspects. The level of physical and mental disability in stroke patients can affect the quality of life. The purpose of this community service is to measure the quality of life using the EQ-5D-5L method to create public awareness of the importance of a healthy lifestyle as a form of prevention of a disease compared to if they are sick they continue to take expensive treatment. Another goal is stroke training to increase the immunity of the human body so that it is susceptible to disease and makes life healthy without having to depend on drugs. Activities include education on stroke prevention as early as possible, antistroke-antistress exercises, distribution of stroke posters and measuring patient quality. This activity was attended by 44 prolanists. A total of 44 participants. There was a significant difference (p<0.05) in the level of knowledge of the participants after the three stages of stroke prevention counseling, which included material related to stroke disease, material on stroke risk factors, material on identifying early symptoms of stroke and material on smart ways to prevent stroke. The results of measuring the quality of life with the final EQ-5D-5L method are 0,83 influenced by age and occupation, which shows a P value <0.05. The results of the final VAS measurement 86,30.... were not affected by patient characteristics, indicated by a P value > 0.05. The purpose of this community service activity has succeeded in providing benefits as evidenced by measurements of quality of life showing an increase in EQ-VAS and EQ-5D-5L values, as a result of successful education, increased immunity due to antistroke-antistress exercises. Keywords: Stroke, EQ-5D-5L, EQ-VAS, Quality of life, Immunity